Adaptation of Acidithiobacillus bacteria to metallurgical wastes and its potential environmental risks - Kratosová, Gabriela; Schröfel, Adam; Seidlerová, Jana; Kristofová, Dana (Waste management & research., 2012)
Metallurgical wastes--oxygen converter sludge, dust from cast iron production, lead matte, and slag from recycling of used lead batteries--were treated with Acidithiobacillus bacteria. Bacterial activity and adaptability on waste and some waste mixtures were investigated. Acidithiobacillus bacteria may easily attack oxygen converter sludge, lead matte and slag and affect the mobility of metals. Cast iron dust is not a suitable substrate for applied bacteria due to the absence of reduced sulfur and reduced iron in its mineralogical composition. Nevertheless, the pure culture was able to adapt to the mixture of this waste with slag. Disposal of these metallurgical wastes deserves special attention due to potential attack by microorganisms and consequent pH changes. According to subsequent release of hazardous substances to the environment, this phenomenon can lead to evident environmental risks.
Keywords: Metallurgy; fyziologická adaptace; průmyslový odpad; odpadky - odstraňování; odpad tekutý - odstraňování; Adaptation, Physiological; Industrial Waste; Environmental Pollutants; Spectrophotometry, Atomic; Refuse Disposal; Species Specificity; spektrofotometrie atomová; Acidithiobacillus; Waste Disposal, Fluid; druhová specificita; látky znečišťující životní prostředí; hutnictví